To Be Or Not To Be On The Internet: A Multidimensional Tool For Studying Online Anonymities - Eklund, Lina; Von Essen, Emma; Jonsson, Fatima (AoIR Selected Papers of Internet Research, 2017)
Anonymity on the internet has become a contentious issue; it both protects freedom of speech and hampers accountability of crime and harassment. Traditionally anonymity has been construed as a dichotomy, you are anonymous or not; however, previous research have shown that this is too narrow a definition online. In this study we 1) draw on the multidisciplinary literature concerning online anonymity 2) derive at a multi-layered conceptual model for studying online anonymity, and 3) explore the complexity as different facets of anonymity interact and interlink by drawing on two empirical examples, online auction sites and massive multi-player online gaming. Our results point to four main facets of anonymity that together make up online anonymity: Legal (state/intra-state and commercial regulations), factual (nonymity/pseudonymity/and being known), social (in-group/out-group behaviour), and physical (embodiment/emotion) anonymity. These are not mutually exclusive, nor dichotomous, but part of a continuum. Drawing on our empirical examples, we conclude that anonymity online can be seen as a process guided by regulations on both a legal and commercial scale that relies heavily on our own perception of being anonymous along factual, social, and physical lines. We argue that we should talk about anonymities, in plural, instead of anonymity.